Faktor yang berhubungan dengan tingkat depresi pada pasien gagal ginjal kronis yang menjalani tindakan hemodialisa - Indra Maulana; Iwan Shalahuddin; Taty Hernawaty (Holistik Jurnal Kesehatan, 2020)
Psychosocial factors: The depression level  in patients with chronic kidney disease maintained on dialysisBackground: Chronic renal failure undergoing hemodialysis therapy in the world is almost 1.5 million people, and in Indonesia there are approximately 0.2 people with chronic renal failure undergoing hemodialysis therapy. The impact of hemodialysis on the physical that will occur in patients become weak tired in living their daily lives, against the psychological impact that will occur on sleep problems, impurity and depression, the impact on social and economic conditions that will occur to patients on social relationships, and on the environment the client will also have an impact on the social environment in which he lives. Therefore hemodialysis therapy will have an impact on the quality of life of patients.Purpose: To determine Psychosocial factors: the depression level  in patients with chronic kidney disease maintained on dialysisMethod: A descriptive correlational study by a cross sectional design approach. The sample used was 40 respondents, data collection techniques using questionnaires and direct observation with results calculated based on the total answers to questions given by respondents with criteria: score <17 = no sign of depression, score 18-24 = mild depression, score 25-34 = moderate depression and a score of 35-51 = severe depression, while the bivariate test used chi-squareResults: There was a relationship among factors such as: age, educational, sex, duration of maintaine of hemodialysis therapy and sleep patterns with the depression level in patients with chronic kidney disease under maintained on dialysis at Garut dr. Slamet Hospital.Conclusion: Health workers (nurses) to provide motivational and therapeutic informing in implementing hemodialysis therapy so that patients are more excited and better understand the importance of hemodialysis and to reduce the level of depression.Keywords: Depression level; Patients; Chronic kidney disease; DialysisPendahuluan: Penyakit gagal ginjal kronik yang menjalani terapi hemodialisis di dunia hampir sekitar 1,5 juta orang, dan di indonesi hampitr sekitar 0,2 jiwa penderita gagal ginjal kronik yang menjalani terapi hemodialisis. Dampak hemodialisis terhadap fisik yang akan terjadi pada pasien menjadi lemah lelah dalam menjalani kehidupan sehari-hari, terhadap psikologis dampak yang akan terjadi pada masalah tidur, kecemasaan dan depresi, dampak terhadap sosial dan ekonomi yang akan terjadi pada pasien pada hubungan sosialnya, dan pada lingkungan klien juga akan berdampak pada sosial lingkungan dimana dia tinggal. Maka dari itu terapi hemodialisis akan berdampak pada kualitas hidup pasien.Tujuan: Mengetahui faktor-faktor yang berhubungan dengan tingkat depresi pada pasien gagal ginjal kronis yang menjalani tindakan HemodialisaMetode: Menggunakan rancangan deskriptif korelasional dengan pendekatan desain cross sectional dengan sampel sebanyak 40 responden, teknik pengambilan data menggunakan kuesioner dan observasi langsung dengan hasil dihitung berdasarkan  total jawaban dari pertanyaan yang diberikan responden dengan kriteri skor <  17 = tidak ada depresi,  skor 18-24 = depresi ringan,  skor 25-34= depresi sedang dan skor 35-51= depresi berat                        sedangkan uji bivariat menggunakan chi-square.Hasil: Menunjukan adanya hubungan antara faktor : usia, pendidikan, jenis kelamin, lamanya periode menjalani terapi hemodialisa dan pola tidur. Semua faktor tersebut sangat  berhubungan dengan tingkat depresi pada pasien gagal ginjal kronik yang menjalani tindakan hemodialisa di Ruang Hemodialisa RSUD dr. Slamet Garut.Simpulan: Petugas kesehatan (perawat) agar memberikan motivasi dan terapeutik informing dalam pelaksanaan terapi hemodialisa agar pasien lebih bersemangat dan lebih memahami pentingnya hemodialisa serta untuk mengurangi tingkat depresi.